Otherwise: imagining queer feminist art histories - Jones, Amelia; Silver, Erin (Rethinking art's histories, 2016)
Otherwise: Imagining queer feminist art histories" is the first publication to address queer feminist politics, methods and theories in relation to the visual arts, including new media, installation and performance art. Despite the crucial contribution of considerations of 'queer' to feminism in other disciplines of the humanities, and the strong impact of feminist art history on queer visual theory, a visible and influential queer feminist art history has remained elusive. This book fills the gap by offering a range of essays by key North American and European scholars, both emerging and renowned, who address the historiographic and political questions arising from the relationship between art history and queer theory in order to help map exclusions and to offer models of a new queer feminist art historical or curatorial approach.
Keywords: LGBTQIA2+; amérique du nord; amériques; approches et analyses; art contemporain; arts; arts visuels et médiatiques; cours; discipline; europe; har4600; histoire de l'art; identités LGBTQIA2+; installation; performance; premier cycle; queer; régions géographiques; thématiques; transféminisme

Artistes femmes: la parenthèse enchantée: XVIIIe-XIXe siècles - Sofio, Séverine (CNRS éditions, 2016)
Entre 1750 et 1850, l'univers des beaux-arts connaît de profondes mutations, dont l'une des conséquences est la banalisation d'une image positive de la dame artiste. Progressivement, des barrières s'abaissent, des contraintes se desserrent et la pratique de la peinture est rendue plus accessible aux femmes. S'ouvre alors une période de créativité foisonnante associée aux noms--parfois oubliés aujourd'hui--d'Elisabeth Vigée-Lebrun, Adélaïde Labille-Guiard, Marie-Guillemine Benoist, Marguerite Gérard, Constance Mayer, Victoire Jaquotot, Lizinka de Mirbel, Rosa Bonheur ...
Keywords: 1700-1799; 1800-1899; arts; cours; discipline; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; pol4022; premier cycle; périodes historiques; régions géographiques; thématiques